Thermal Hydrogen Reduction For Synthesis Of Gold Nanoparticles In The Nanochannels Of Mesoporous Silica Composite - Mohamad Azani Jalani; Leny Yuliati; Hendrik O. Lintang (Penerbit UTM Press, 2024)
Gold nanoparticles (AuNPs) with small particle size have been difficult to be synthesized due to their strong agglomeration. Herein we report that the nanochannels of mesoporous silica synthesized from template sol-gel synthesis were utilized to prepare AuNPs by employing thermal hydrogen reduction. Mesoporous silica composite with an interpore distance of 4.1 nm was successfully fabricated as a thin film by an amphiphilic trinuclear gold(I) pyrazolate complex ([Au3Pz3]C10TEG) as a template. In contrast to calcination method of this composite and the bulk [Au3Pz3]C10TEG complex at 450ÂºC for 3 h, thermal hydrogen reduction at 250ÂºC for 2 h showed transmission electron microscope (TEM) images and diffraction pattern with smaller particle size (14.5 nm) and more homogenous distribution of AuNPs with up to 44% of the particle size in the range of 10 to 20 nm. The decreasing of average particle size in this new strategy indicated by the red-shifting of the surface plasmon resonance (SPR) band from 518 (AuNPs from the bulk [Au3Pz3]C10TEG complex) and 544 (calcination) to 558 nm.